1988
DOI: 10.1093/brain/111.5.1173
|View full text |Cite
|
Sign up to set email alerts
|

Ideational Apraxia

Abstract: Ideational apraxia was investigated in 20 left brain-damaged patients with tests requiring the demonstration of how objects are used. On a multiple object use test the most frequent errors were those of omission, misuse and mislocation, while sequence errors were rare. Patients also failed on a single object use test, which showed a correlation of 0.85 with the multiple object use test. Neither of these tests was significantly correlated with an ideomotor apraxia test (imitation of movements). Ideational aprax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
267
2
15

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 420 publications
(295 citation statements)
references
References 0 publications
11
267
2
15
Order By: Relevance
“…These findings are in line with clinical studies, showing that cerebral lesions in middle frontal and parietal circuits can cause ideational apraxia (Hécaen, 1972;Bolognini et al, 2015;De Renzi and Lucchelli, 1988). Further investigations will be necessary to explore whether patients with movement disorders, such as patients with Parkinson's disease, would engage the same neural circuits during motor ideation.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…These findings are in line with clinical studies, showing that cerebral lesions in middle frontal and parietal circuits can cause ideational apraxia (Hécaen, 1972;Bolognini et al, 2015;De Renzi and Lucchelli, 1988). Further investigations will be necessary to explore whether patients with movement disorders, such as patients with Parkinson's disease, would engage the same neural circuits during motor ideation.…”
Section: Resultssupporting
confidence: 82%
“…In conclusion, ideational apraxia might not constitute a higherorder programming deficit of movement per se, but a combination of executive, language, and memory deficits or a diffuse reduction of cognitive resources (Gross and Grossman, 2008). Different lesion sites have been indicated as responsible for ideational apraxia, showing an involvement of mainly left temporo-parieto-occipital regions (Hécaen, 1972;Bolognini et al, 2015) even if patients with ideational apraxia have also been reported following frontal lesions, or basal ganglia damage (De Renzi e Lucchelli, 1988;Manuel et al, 2013;Huey et al, 2009). Patients with ideational apraxia can retain mental imagery abilities (Tomasino et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one anticipation error commonly produced by patients involves attempting to pour from a sealed container (e.g., De Renzi & Lucchelli, 1988;Schwartz et al, 1991). Within the domain investigated by Botvinick and Plaut (2004), this error might be manifest by the model attempting to pour from the coffee, sugar, or cream packets before opening them.…”
Section: On the Importance Of The Training Setmentioning
confidence: 99%
“…However, these are difficult to interpret due to terminological confusions and poverty of neuroanatomical information. It was claimed that ideational apraxia reflects an impairment of the praxis conceptual system including loss of knowledge related to tools [De Renzi and Lucchelli, 1988], but others argued that the term must be restricted to action sequencing disorders [Poeck, 1983]. Subsequently, Ochipa et al [1989] proposed the term conceptual apraxia to qualify disturbances of the action semantic system except action-sequencing disorders.…”
Section: Action Semantic Systemmentioning
confidence: 99%